Improvement of Community Governance to Support Slum Upgrading Programs in Indonesia - Asyrafinafilah Hasanawi; Hasanawi Masturi; Adib Hasanawi (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
Urbanism's impact creates land scarcity as a result of an imbalance in urban land between supply and demand. As a developing country, Indonesia is still striving to overcome the slum area and provide decent housing for low - income groups. In fact, the city is owned by everyone, so slum people and other low - income groups have the right to the city to enjoy the results of development and its facilities and infrastructure, including decent urban living spaces. These areas are government challenges and opportunities to provide the best housing services for poor or marginal communities. Over the past decades, slum upgrading has become a global solution to overcome slum problems. It relies on the concept of ' self - help ' in which community participation is used as a means of improving and sustaining the quality of life of slum dwellers. The number of researches was carried out to analyze the level of community participation in slum upgrading, but not many analyze the level of governance in slum upgrading. The purpose of this research is to analyze the performance of Indonesia governance in achieving successful slum upgrading by using a single case study of one of Indonesia's slum upgrading projects, namely the Neighborhood Upgrading and Shelter Sector Project (NUSSP). The transition from centralized to decentralized governance has become the biggest challenge in implementing slum upgrading in Indonesia, especially on issues of political engagement, coordination, and cooperation, financial sustainability, tenure security, continuity, and institutionalization. This research has led to the conclusion that transitional Indonesia requires a unified strategy that combines some forms of centralized governance with some forms of decentralized governance. Finally, the concepts of ' self - help, ' ' less governance, ' and ' development from below ' proposed as the original concepts of slum upgrading could not work independently. Strong intervention, adequate governance and ' development from above ' are really needed to achieve successful slum upgrades. Keywords: slum; slum upgrading; governance; sustainability; community participation.